2021
DOI: 10.3389/fcimb.2021.634981
|View full text |Cite
|
Sign up to set email alerts
|

16S rDNA Full-Length Assembly Sequencing Technology Analysis of Intestinal Microbiome in Polycystic Ovary Syndrome

Abstract: ObjectiveTo study the characteristics and relationship of the gut microbiota in patients with polycystic ovary syndrome (PCOS).MethodWe recruited 45 patients with PCOS and 37 healthy women from the Reproductive Department of Shengjing Hospital. We recorded their clinical indexes, and sequenced their fecal samples by 16S rDNA full-length assembly sequencing technology (16S-FAST).ResultWe found decreased α diversity and different abundances of a series of microbial species in patients with PCOS compared to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Further studies found that transplantation of fecal microbiota from women with PCOS would lead to the elevated proportion of disrupted ovarian functions, insulin resistance and infertility [15]. Also, some studies reported that Bacteroides were enriched in the PCOS women (35). Zhang et al found that the larger proportion of Bacteroides in PCOS women by analyzing the stool microbiome.…”
Section: Gut Microbiome In Pcos Patientsmentioning
confidence: 99%
“…Further studies found that transplantation of fecal microbiota from women with PCOS would lead to the elevated proportion of disrupted ovarian functions, insulin resistance and infertility [15]. Also, some studies reported that Bacteroides were enriched in the PCOS women (35). Zhang et al found that the larger proportion of Bacteroides in PCOS women by analyzing the stool microbiome.…”
Section: Gut Microbiome In Pcos Patientsmentioning
confidence: 99%
“…Prevotella might be one of the identifier in IR influenced healthy weight PCOS women and can be correlated with the PCOS disease as Prevotella is a prominent SCFA‐producing bacterium in the intestine, and it can also generate anti‐inflammatory compounds that can facilitate the development of regulatory T cells in the gut, thereby lowering inflammation 79 . Another finding reported that PCOS‐IR women have predominantly Bacteroidetes enterotype 80 . As a result of these altered microbiota, LPS containing microbes and steroid production pathways are enhanced in PCOS‐IR women 78 .…”
Section: Insulin Resistance and Microbiomementioning
confidence: 99%
“…79 Another finding reported that PCOS-IR women have predominantly Bacteroidetes enterotype. 80 As a result of these altered microbiota, LPS containing microbes and steroid production pathways are enhanced in PCOS-IR women. 78 Inflammatory mediators can activate serine, resulting in enhanced phosphorylation, suppressed tyrosine kinase activity, and significantly reduced insulin-stimulated receptor tyrosine phosphorylation obstructing insulin receptor activation and downstream cascade activation thus, lowering IRS-1 function.…”
Section: Inflammatory Pathwaysmentioning
confidence: 99%
“…Next, data from electrophoresis and the measurements of Qubit concentrations were assembled for quality control before Illumina NovaSeq 6000 sequencing (Illumina, USA). The detailed process was reported in a previously published study ( Dong et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%